Cord blood iron status and vitamin D concentration in newborns of anemic and non-anemic mothers in Makassar, Indonesia - Ridha, Nadirah Rasyid; Massi, Muhammad Nasrum; Fikri, Bahrul; Putri, Sri Hardiyanti; Hidayah, Najdah; Arsyad, Andi Fatimah (Paediatrica Indonesiana, 2024)
Background Iron deficiency (ID) is a common micronutrient problem, especially in pregnant women in developing countries such as Indonesia. Moreover, vitamin D deficiency is also a major concern in worldwide public health. A correlation between anemia, ID, and vitamin D deficiency in children has been identified, but investigations in pregnant women and their newborn babies are still limited. Objective To assess association between iron status and vitamin D levels in umbilical cord blood and maternal anemia. Methods This cross-sectional study involved 109 pregnant women and their newborns. They were divided into two groups, with and without maternal anemia. Collected cord blood (2 mL) was placed in tubes with ethylenediaminetetraacetic acid (EDTA). Plasma ferritin and vitamin D (25-hydroxyvitamin D, 25(OH)D) levels were measured by enzyme-linked immunosorbent assay (ELISA). Results Maternal anemia was found in 60 mothers (55% subjects). The mean cord blood hemoglobin levels for the anemic and non-anemic groups were 15.19 (SD 2.25) g/dL and 15.12 (SD 1.98) g/dL, respectively (P=0.87). Median cord blood ferritin levels were slightly lower in anemic [12.95 (range 0.42-17.69) µg/L] than in non-anemic mothers[13.45 (range 7.10-22.12) µg/L], but were not significantly different (P=0.555). Median cord blood 25(OH)D levels were lower in the anemic group [12.24 (range 8.53-32.99) ng/dL] than in the non-anemic group [14.26 (range 9.84-61.44) ng/dL], but the difference was not significant (P=0.964). Conclusion Maternal anemia was not significantly associated with cord blood hemoglobin, ferritin, or 25(OH)D levels.